2019
DOI: 10.1093/pubmed/fdz058
|View full text |Cite
|
Sign up to set email alerts
|

Rolling back the prison estate: the pervasive impact of macroeconomic austerity on prisoner health in England

Abstract: Prisons offer policymakers an opportunity to address the pre-existing high prevalence of physical and mental health issues among prisoners. This notion has been widely integrated into international and national prison health policies, including the Healthy Prisons Agenda, which calls for governments to address the health needs of prisoners and safeguard their health entitlement during imprisonment, and the Sustainable Development Goals 2030 concerning reducing inequality among disadvantaged populations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…Consistent with prior work [ [30] , [31] , [32] ], this study’s participants identified a rapid deterioration of the existing poor standards of health and decency under austerity. Given the longstanding overcrowding problem within prisons, reducing the number of officers within institutions diminishes interactions between prisoners and staff.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Consistent with prior work [ [30] , [31] , [32] ], this study’s participants identified a rapid deterioration of the existing poor standards of health and decency under austerity. Given the longstanding overcrowding problem within prisons, reducing the number of officers within institutions diminishes interactions between prisoners and staff.…”
Section: Discussionsupporting
confidence: 84%
“…Compatible with prior research [ 31 , 37 , 55 ], this study drew on the expertise of 27 of an invited 73 (38 %) national health experts with experience devising and implementing prison health policies across England, whether through the government or for non-governmental organisations. As such, they reflected a broad composition of England’s prison health terrain, political and policy elites in an ideal position to understand the impact of austerity measures.…”
Section: Methodsology and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving equivalence of care for prisoners requires investment of a higher level of resource than for community patients, to create prison-focussed solutions and pathways that exceed, rather than fail, community standards of care [ 30 ]. These investments will transfer out into the community, improving the health of society overall [ 31 ]. Prison healthcare remains an evolving landscape, and hospital care is one of many areas requiring further research with respect to equivalence.…”
Section: Discussionmentioning
confidence: 99%
“…However, since austerity measures imperil prisoners’ health, the level of punishment has arguably increased beyond the loss of liberty. 22 Due to the lack of prison staff, prisoners missed 15% of medical appointments on average. 8 Furthermore, two-thirds of prisoners waited longer than 14 days to be seen by acute mental-health professionals, while some waited more than 12 months to be transferred to a secure mental-health hospital.…”
Section: Impact On Prisoners and Prison Staffmentioning
confidence: 99%